Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures